2022
DOI: 10.1097/fch.0000000000000340
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Health Care Access, Utilization, and Experiences Among LGBTQ+ Subgroups in the Southern United States

Abstract: Lesbian, gay, bisexual, transgender, queer, and other sexual and gender minority (LGBTQ+) individuals experience health inequities and barriers to accessing appropriate, affirming care. Little is known about differing health care experiences within the LGBTQ+ population, particularly among individuals living in underserved areas. This study explored health care experiences and utilization among LGBTQ+ subgroups: lesbian and gay cisgender individuals (n = 258), bisexual+ cisgender individuals (n = 71), and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In the context of psychotherapy, multiple forms of SGM-based microaggressions have been identified that can influence intentions to seek mental health services 32–34 . The lack of report of these barriers identified in other samples of SGM individuals should be interpreted cautiously, particularly for GM individuals who endorsed more discriminatory healthcare experiences compared with lesbian and gay individuals in a larger sample from our health needs assessment 35 . It also is possible that participants’ reported difficulties in even obtaining an appointment meant that they never had the opportunity to experience either microaggressions toward or microaffirmations of their SGM identities by providers.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the context of psychotherapy, multiple forms of SGM-based microaggressions have been identified that can influence intentions to seek mental health services 32–34 . The lack of report of these barriers identified in other samples of SGM individuals should be interpreted cautiously, particularly for GM individuals who endorsed more discriminatory healthcare experiences compared with lesbian and gay individuals in a larger sample from our health needs assessment 35 . It also is possible that participants’ reported difficulties in even obtaining an appointment meant that they never had the opportunity to experience either microaggressions toward or microaffirmations of their SGM identities by providers.…”
Section: Discussionmentioning
confidence: 94%
“…[32][33][34] The lack of report of these barriers identified in other samples of SGM individuals should be interpreted cautiously, particularly for GM individuals who endorsed more discriminatory healthcare experiences compared with lesbian and gay individuals in a larger sample from our health needs assessment. 35…”
Section: Discussionmentioning
confidence: 99%
“…[103][104][105][106][107] Finally, providers universally expressed supportive attitudes towards gender-affirming practices. To make a maximally scalable intervention appropriate for use in regions with more transphobic attitudes, 91,108 future studies should recruit and elucidate the needs of providers who express hostility and/or hesitancy about genderaffirming practices. [109][110][111][112] An additional strength of GAP is its evidence-informed nature.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, queer, questioning, and transgender individuals might encounter more significant healthcare obstacles compared to their lesbian, gay, and cisgender counterparts (Macapagal et al, 2016). Notably, transgender and gender-diverse participants face higher levels of discriminatory experiences and increased barriers to accessing care, indicating the importance of targeted interventions to improve their healthcare experiences and outcomes (Holt et al, 2023). Addressing these disparities in health care requires policy, research, and practice changes, focusing on tailored health services that meet the unique needs of LGBTI individuals (Zeeman et al, 2019).…”
Section: Sleep Health Disparities Among Racial-ethnic Minority Womenmentioning
confidence: 99%